2008
DOI: 10.1007/s00296-008-0528-5
|View full text |Cite
|
Sign up to set email alerts
|

Is joint hypermobility important in prepubertal children?

Abstract: The purpose of this study was to investigate serum prolidase activity and its relationship with collagen metabolism and joint hypermobility, and to determine the prevalence and characteristics of joint hypermobility in prepubertal children. Serum prolidase activity was measured spectrophotometrically. Joint hypermobility was defined using Beighton criteria. The children underwent complete history and physical examination. Serum levels of prolidase were lower in the hypermobile group compared with controls and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…In a study, Galicka et al [21] found lower prolidase enzyme activity in osteogenesis imperfecta cells. In another study conducted on children with joint hypermobility, who met the Beighton diagnostic criteria, Yazgan et al [18] found lower prolidase activity in the patients compared to the controls, which was not statistically significant. Both studies concluded that decreased prolidase activity might affect the cellular growth and the collagen metabolism.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…In a study, Galicka et al [21] found lower prolidase enzyme activity in osteogenesis imperfecta cells. In another study conducted on children with joint hypermobility, who met the Beighton diagnostic criteria, Yazgan et al [18] found lower prolidase activity in the patients compared to the controls, which was not statistically significant. Both studies concluded that decreased prolidase activity might affect the cellular growth and the collagen metabolism.…”
Section: Discussionmentioning
confidence: 98%
“…Prolidase is an enzyme which can influence the collagen structure in patients with BJHS. There is a study in the literature which evaluates the prolidase activity in children with hypermobility [18]. The current work is the first study to investigate the prolidase activity in adult females.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations